A novel hybrid design and modelling of a customised graded Ti-6Al-4V porous hip implant to reduce stress-shielding: An experimental and numerical analysis - Naghavi, Seyed Ataollah; Tamaddon, Maryam; Garcia-Souto, Pilar; Moazen, Mehran; Taylor, Stephen; Hua, Jia; Liu, Chaozong (Frontiers in Bioengineering and Biotechnology, 2023)
Stress shielding secondary to bone resorption is one of the main causes of aseptic loosening, which limits the lifespan of hip prostheses and exacerbates revision surgery rates. In order to minimise post-hip replacement stress variations, this investigation proposes a low-stiffness, porous Ti6Al4V hip prosthesis, developed through selective laser melting (SLM). The stress shielding effect and potential bone resorption properties of the porous hip implant were investigated through both in vitro quasi-physiological experimental assays, together with finite element analysis. A solid hip implant was incorporated in this investigation for contrast, as a control group. The stiffness and fatigue properties of both the solid and the porous hip implants were measured through compression tests. The safety factor of the porous hip stem under both static and dynamic loading patterns was obtained through simulation. The porous hip implant was inserted into Sawbone / PMMA cement and was loaded to 2,300 N (compression). The proposed porous hip implant demonstrated a more natural stress distribution, with reduced stress shielding (by 70%) and loss in bone mass (by 60%), when compared to a fully solid hip implant. Solid and porous hip stems had a stiffness of 2.76 kN/mm and 2.15 kN/mm respectively. Considering all daily activities, the porous hip stem had a factor of safety greater than 2. At the 2,300 N load, maximum von Mises stresses on the hip stem were observed as 112 MPa on the medial neck and 290 MPa on the distal restriction point, whereby such values remained below the endurance limit of 3D printed Ti6Al4V (375 MPa). Overall, through the strut thickness optimization process for a Ti6Al4V porous hip stem, stress shielding and bone resorption can be reduced, therefore proposing a potential replacement for the generic solid implant.